2008
DOI: 10.1002/ange.200804757
|View full text |Cite
|
Sign up to set email alerts
|

Catalyzed Dehydrogenative Coupling of Primary Alcohols with Water, Methanol, or Amines

Abstract: Gute Zusammenarbeit von Metallzentrum und Liganden ist der Schlüssel zur hohen Aktivität des Rhodiumamidokomplexes 1 in den dehydrierenden Kupplungen primärer Alkohole mit Wasser, Methanol oder Aminen (einschließlich Ammoniak) zu Carbonsäuren, Methylestern bzw. Amiden. Der katalytische Prozess verläuft unter milden Bedingungen in der Gegenwart des zurückgewinnbaren Wasserstoffakzeptors A, und der vielstufige Mechanismus wurde durch Rechnungen aufgeklärt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(51 citation statements)
references
References 27 publications
1
50
0
Order By: Relevance
“…Several reports on amide formation by dehydrogenative coupling of amines with alcohols appeared later. [18] Unlike complex 1, the analogous PNP complex 2 (or complex 3 in the presence of an equivalent of base) catalyzes the coupling of amines with alcohols to form imines rather than amides with liberation of H 2 and H 2 O (Scheme 2, Eq. (2)).…”
mentioning
confidence: 99%
“…Several reports on amide formation by dehydrogenative coupling of amines with alcohols appeared later. [18] Unlike complex 1, the analogous PNP complex 2 (or complex 3 in the presence of an equivalent of base) catalyzes the coupling of amines with alcohols to form imines rather than amides with liberation of H 2 and H 2 O (Scheme 2, Eq. (2)).…”
mentioning
confidence: 99%
“…We show that in this device, a metal complex evolves through fast chemical equilibria to form specific catalysts for alcohol dehydrogenation, aldehyde dehydrogenation, and H + /electron transfer. We recently reported that the organometallic complex [Rh(trop 2 N)(PPh 3 )] (1) catalyses the oxidation of primary alcohols to give carboxylic acid derivatives in the presence of hydrogen acceptors A such as RR'C = O, olefins, or palladium nanoparticles in either homogeneous [9,10] or heterogeneous phase (Scheme 1). [11] The amido complex 1 is simply accessed by deprotonation of the precursor complex [Rh(OTf)-(trop 2 NH)(PPh 3 )] (2) under basic conditions (OTf = trifluoromethanesulfonate).…”
mentioning
confidence: 99%
“…Ruthenium complexes, and especially NHC-compounds, have been the most widely studied [94], albeit highly efficient processes promoted by rhodium or silver have also been described [112,113]. In regard to ruthenium, both in-situ-generated catalytic systems (Table 1) [114][115][116][117][118][119][120][121][122][123] as well as well-defined catalysts 38-44 ( Figure 10) [124][125][126][127][128][129][130][131] have been reported.…”
Section: Scheme 23 Synthesis Of 36-disubstituted-piperazine-25-diomentioning
confidence: 99%
“…Gold-and rhodium-catalyzed acylations of ammonia have been reported [112,132], but similar transformations promoted by homogeneous ruthenium catalysts still remain unknown. Such a reaction could only be performed employing a heterogeneous ruthenium-based system under aerobic conditions.…”
Section: Scheme 23 Synthesis Of 36-disubstituted-piperazine-25-diomentioning
confidence: 99%